HUBUNGAN DISIPLIN KERJA DENGAN PENINGKATAN KINERJA PETUGAS KESEHATAN DI PUSKESMAS TULADENGGI KECAMATAN TELAGA BIRU KABUPATEN GORONTALO - Sabirin B Syukur; Nikartin Pakaya (-, 2021)
Puskesmas constitutes one of the most health facilitation that give health services to society is confront quality service. The society demand to the Puskesas’s worker  to increase performance and professionalism. In order to get society satisfaction and  to reach a good performance needed disciplined in working. this research aim to get relationship job’s discipline with health officer raising performance at puskesmas tuladenggi. Observational design that is utilized is descriptive correlation with cross sectional survey's approaching. population in observational is PNS and  amount to 47 person. Meanwhile sample took by saturated sampling tech, with the meaning all population was made by sampel.pengumpulan data did by observation tech and kuesioner. to test dianalisis's data by use of univariat's analysis tech and bivariate. For univariat's data analysis did by analisis presentation to see distribution each variable. meanwhile for dianalisis's bivariate data analysis with approaching statisticaling to utilize Chi Square's quiz formula.